MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR MELALUI PENERAPAN PENDEKATAN SCIENTIFIC MATERI REDOKS PADA SISWA KELAS X MS 5 SMA NEGERI 2 BANJARMASIN - Desi Amelia; Syahmani Syahmani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. A research on the application of the Scientific approach to redox learning in the classroom X MS 5 SMA Negeri 2 Banjarmasin academic year 2013/2014. This research aimed to determine: (1) the activity of the teacher (2) increase the activity of students (3) increase students' science process skills (4) enhancement of cognitive and affective outcomes. This research method uses design of classroom action research (PTK) with 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class X MS 5 SMA Negeri 2 Banjarmasin the number of 34 people. The research instrument is a test instrument type process skills worksheets, achievement test objective type questions totaling 15 questions and non-test. The results stated that (1) the implementation of the cycle I of teachers teaching process is fair increase to very good in the cycle II (2) increase the activity of students from cycle I to cycle II with a score of 9 (3) increase students' science process skills from the cycle I to cycle II with a score of 12,2 (4) increase students' mastery of cognitive learning outcomes of the cycle I to the cycle II of 12,5% and affective learning outcomes of character behavior and social skills of students cycle I was quite good at rising to the cycle II.Keywords: science process skills, scientific approaches, redox.